2021
DOI: 10.3389/fonc.2021.615704
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Stem Cells as Immunotherapeutic Targets: Advancements and Challenges

Abstract: Glioblastoma is the most common and lethal primary brain malignancy. Despite major investments in research into glioblastoma biology and drug development, treatment remains limited and survival has not substantially improved beyond 1–2 years. Cancer stem cells (CSC) or glioma stem cells (GSC) refer to a population of tumor originating cells capable of self-renewal and differentiation. While controversial and challenging to study, evidence suggests that GCSs may result in glioblastoma tumor recurrence and resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 129 publications
0
44
0
Order By: Relevance
“…Despite advances in both treatment and biological understanding, prognosis remains poor. Other than the modest benefit demonstrated by the addition of temozolomide to radiotherapy, and TTField therapy to chemoradiotherapy, modern-day regimens have not significantly improved overall survival in the past 40 years [2][3][4][5]. According to an National Cancer Database study, long-term survivorship (over three years) in those with GBM is only ~ 9% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in both treatment and biological understanding, prognosis remains poor. Other than the modest benefit demonstrated by the addition of temozolomide to radiotherapy, and TTField therapy to chemoradiotherapy, modern-day regimens have not significantly improved overall survival in the past 40 years [2][3][4][5]. According to an National Cancer Database study, long-term survivorship (over three years) in those with GBM is only ~ 9% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the brain tumor shows a highly immunosuppressive microenvironment, which attenuates the immune responses to tumor cells, making their condition even worse (Gangoso et al, 2021). In addition, because of its high intratumoral heterogeneity, the brain tumor has a therapeutic resistance to many drugs and a high recurrence rate (Piper et al, 2021). Hence, the development of vehicles for crossing BBB and tumor targeting is of importance for brain tumor therapy.…”
Section: Brain Tumorsmentioning
confidence: 99%
“…found that trefoil factor 3 (TFF3) has antidepressant effects in animal models, but the dose needs to be high for therapeutic application (Shi et al., 2012 ). To further increase the concentration of TFF3 in the brain, they developed cRGD-modified liposomes (cRGDL) with a high affinity to integrin receptors on monocytes (Qin et al., 2015 ). The monocyte-cRGDL (loaded with TFF3) complexes, with BBB-crossing and brain-targeting abilities, increased the brain distribution of TFF3 and exhibited enhanced antidepressant effects and behavioral response of TFF3 treatment.…”
Section: Application Of Blood Cell-based Biomimetic Delivery Systemsmentioning
confidence: 99%
“…Radioresistance of GB GB tumors have been identified as therapy resistant due to multiple molecular mechanisms including inadequate drug blood-brain barrier (BBB) passage, intra-and intertumoral heterogeneity, redundant signaling pathways resulting in rescue mechanisms, adaptive radioresistance and an immunosuppressive tumor micro-environment (TME) promoted by a chronic state of hypoxia (15,(42)(43)(44). Hypoxic niches limiting the formation of reactive oxygen species (ROS) and a hyperactivation of the DNA damage response machinery induced by glioma stem cells (GSC) contribute to glioma radioresistance (44,45). In addition, a crosstalk between TME populations via shared pathways, such as STAT3, Wnt and Notch play a role (15,46).…”
Section: Radiotherapy and Radioresistance Of Gbmentioning
confidence: 99%